The Duality of Mimetic Desire and the Free Will of Existence in Unconscious: In the Context of Syed Waliullah’s ’Bohipir’ - Talukder, Kripakona (Jagannath University Journal of Arts, 2026)
Bohipir, written by Syed Waliullah, is a significant and unique work created in the history of Bangladeshi drama, where the complex conflict between religion, society and individual identity is portrayed. On one hand, the play reveals the collapse of the decaying feudal system, while on the other, it exposes the rise of Sufi-based religious authority rooted in faith. Simultaneously, it presents two young individuals, symbolizing youth, who step out of their households using their free will in search of something new, thereby asserting their existential identity. According to Sartre, human beings create their own identity through the exercise of free will; in this play, the young characters become symbols of that very freedom. On the contrary, by imitating the desires of others, they construct their own desires and become entangled in a mimetic conflict of desire with one another. Using descriptive and analytical methods, this research article attempts to explain how the duality between the mimetic desire of René Girard and the existential free will of Jean Paul Sartre is manifested in the play. It explores how the unconscious imitation of desire and the conscious exercise of existential free will and clash within the characters’ psyches in Bohipir. Jagnnath University Journal of Arts,v-15, i-2, 2025:p14-24